2019
DOI: 10.4236/ojn.2019.910077
|View full text |Cite
|
Sign up to set email alerts
|

Time Management of the Clinical Nurses at Public Hospital in Bangladesh

Abstract: Nursing is a very intense and focused career, so picking the right time and its proper management can help to relieve personal stress, manage tasks properly and achieve patients and organizational outcome. Objective: This study aimed to explore perceived time management skill of the clinical nurses. Methods: This was a descriptive correlational study design using simple random sampling. A total of 77 clinical nurses working in Mugda Medical College Hospital, Dhaka, Bangladesh were selected as study participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
2
0
0
Order By: Relevance
“…The participants reported moderate levels of time management (80.3%), which is consistent with the ndings of studies conducted by Yunitasari et al (2022), Hashemizadeh et al (2013) and Heydari et al(2012) [32,39,40]. In contrast, a study by Barua et al (2019) in Bangladesh reported poor time management among nurses, which differs from the current study's ndings [41]. This difference may be attributed to cultural, social, and managerial factors prevailing in the respective nursing units.…”
Section: Discussionsupporting
confidence: 89%
“…The participants reported moderate levels of time management (80.3%), which is consistent with the ndings of studies conducted by Yunitasari et al (2022), Hashemizadeh et al (2013) and Heydari et al(2012) [32,39,40]. In contrast, a study by Barua et al (2019) in Bangladesh reported poor time management among nurses, which differs from the current study's ndings [41]. This difference may be attributed to cultural, social, and managerial factors prevailing in the respective nursing units.…”
Section: Discussionsupporting
confidence: 89%
“…Educational level, however, was not associated with time-wasting behavior in this study. Tis result aligns with fndings from a study in Bangladesh that failed to establish a relationship between educational level and time management skills [32]. In contrast, a study in Iran found signifcant positive correlations between time management skills and age, education, job experience, and managerial experience, probably because this study did not adjust for potential confounding efects [16].…”
Section: Discussionsupporting
confidence: 79%